The ritual eaudiobook - Nevill, Adam (Tantor Media, 2018)
When four old University friends set off into the Scandinavian wilderness of the Arctic Circle, they aim to briefly escape the problems of their lives and reconnect with one another. But when Luke, the only man still single and living a precarious existence, finds he has little left in common with his well-heeled friends, tensions rise. With limited experience between them, a shortcut meant to ease their hike turns into a nightmare scenario that could cost them their lives. Lost, hungry, and surrounded by forest untouched for millennia, Luke figures things couldn't possibly get any worse. But then they stumble across an old habitation. Ancient artifacts decorate the walls and there are bones scattered upon the dry floors. The residue of old rites and pagan sacrifice for something that still exists in the forest. Something responsible for the bestial presence that follows their every step. As the four friends stagger in the direction of salvation, they learn that death doesn't come easy among these ancient trees . . .